Eosinophilic homogeneous intracytoplasmic inclusion bodies: Unique viral cytopathic changes associated with epidermodysplasia verruciformis and human papillomavirus type 49. (21st March 2022) - Bartley, Brooke R.; Huen, Auris; Rady, Peter L.; Tyring, Stephen K.; Nagarajan, Priyadharsini; Aung, Phyu P.; Curry, Jonathan L.; Ivan, Doina; Torres‐Cabala, Carlos A.; Prieto, Victor G.; Cho, Woo Cheal
Abstract: Epidermodysplasia verruciformis (EDV) is a rare genodermatosis that predisposes affected individuals to persistent infection with certain types of human papillomavirus (HPV), particularly those that belong to the genus beta‐HPV, including HPV‐5 and HPV‐8, which carry high oncogenic potential. There are three main HPV‐related viral cytopathic changes in cutaneous verrucae in terms of intracytoplasmic inclusion bodies (ICBs), namely, granular, filamentous, and homogeneous type ICBs. To date, only HPV‐4, HPV‐60, and HPV‐65 have been found in association with homogeneous ICBs. We report a unique case of HPV‐49‐associated EDV in a 41‐year‐old woman with common variable immunodeficiency, mycosis fungoides, and multiple cutaneous malignancies, including squamous cell carcinoma and Merkel cell carcinoma who presented with multiple pink papules and hyperpigmented macules on the left upper extremity. One of the skin lesions histopathologically revealed keratinocytic nuclear enlargement with abundant blue–gray cytoplasm, accompanied by hypergranulosis, characteristic of EDV, along with peculiar bright eosinophilic and homogeneous ICBs. To the best of our knowledge, this is the first reported case of EDV with detection of HPV‐49 by genotyping, which features eosinophilic homogeneous ICBs, like those seen in the setting of HPV‐4, HPV‐60, or HPV‐65 infection.